Pacing strategy in simulated cycle time-trials is based on perceived rather than actual distance - Nikolopoulos, V.; Arkinstall, M. J.; Hawley, J. A. (Journal of Science and Medicine in Sport, 2001)
This study determined the pacing strategies and performance responses of six well-trained cyclists/triathletes (peak O2 uptake 66.4+/-3.7 ml x kg(-1) x min(-1), mean+/-SD) during seven simulated time-trials (TT) conducted on a wind-braked cycle ergometer. All subjects first performed a 40 km familiarisation ride (TT1). They were then informed they would be riding a further four 40 km TT for the purpose of a reliability study. Instead, the actual distances ridden for the next three TT were a random order of 34 (TT2), 40 (TT3) and 46 km (TT4). The only feedback given to subjects during TT1-4 was the percentage distance of that ride remaining. During a further 40 km TT (TT5) subjects were allowed to view their heart rate (HR) responses throughout the ride. Despite the significantly different performance times across the three distances (47:23+/-4:23 vs 55:57+/-3:24 vs 65:41+/-3:56 min for the 34, 40 and 46 km respectively, P<0.001), average power output (296+/-48 vs 294+/-48 vs 286+/-40 W) and HR (173+/-11 vs 174+/-12 vs 173+/-12 beats x min(-1)) were similar. The true nature of the first part of the study was then revealed to subjects who subsequently completed an additional 34 km and 46 km TT TT6-7) in which the actual and perceived distance ridden was the same. Power output and HR responses were similar for both unknown (TT2 and TT6) and known (TT4 and TT7) rides for both distances: 296+/-48 vs 300+/-55 W and 173+/-11 vs 177+/-11 beats x min(-1) (34 km) and 286+/-40 vs 273+/-42 W and 173+/-12 vs 174+/-12 beats x min(-1) (46 km). In conclusion, well-trained cyclists rode at similar power outputs and HR during time trials they perceived to be the same distance, but which varied in actual distance from 34 to 46 km.